Tinjauan Hukum Terhadap Pembatalan Akta Pengganti Akta Ikrar Wakaf - Dhea Salsabilah Nadia; La Ode Husein; Nurjaya (Qawanin Jurnal Ilmu Hukum, 2020)
“This Research is aimed at students, especially law faculty students who want to carry out research related to A Legal Review of The Cancellation of The deed to Replace thr Pledge deed of Waqf”. The practice of waqf that occurs in people's lives is not yet fully orderly and efficient. The statement to donate an asset that wants to be donated must be clearly stated by the person who owns the property that wants to be donated along with proof of ownership of the property, but if there is someone who wants to donate the property but is not the legal owner of the object of waqf from the property. that will be donated then a waqf cannot be implemented or has violated the existing regulations regarding waqf, as is the case in the case in Decision Number 349 / Pdt.G / 2013 / PA.Bkls concerning a Cancellation of a Deed in lieu of a Wakaf Pledge located at Siak Regency, Riau Province, where Defendant I clearly did not have a certificate of ownership of the land rights and its relationship with the KUA of Siak Regency as Defendant II who made or issued the Wakaf Pledge Deed. Therefore, the KUA as Defendant II and Defendant I violated several provisions in the Waqf Constitution and the Compilation of Islamic Law. Abstrak “Penelitian ini ditujukan kepada khususnya mahasiswa fakultas hukum yang ingin melaksanakan penelitian terkait Tinjauan Hukum terhadap Pembatalan Akta Pengganti Akta Ikrar Wakaf”. Praktik wakaf yang terjadi dalam kehidupan masyarakat belum sepenuhnya berjalan tertib dan efisien. Pernyataan untuk mewakafkan sesuatu harta benda yang ingin diwakafkan harus benar-benar dinyatakan oleh orang yang memiliki harta benda yang ingin diwakafkan beserta bukti- bukti kepemilikan dari harta bendanya, namun jika adanya seorang yang ingin mewakafkan harta benda tetapi bukan sebagai pemilik sah objek wakaf dari harta yang akan diwakafkan maka suatu perwakafan tidak dapat dilaksanakan atau telah melanggar peraturan yang telah ada mengenain perwakafan, seperti halnya dalam kasus yang ada dalam Putusan Nomor 349/Pdt.G/2013/PA.Bkls tentang suatu Pembatalan Akta Pengganti Akta Ikrar Wakaf yang terletak di Kabupaten Siak Provinsi Riau dimana Tergugat I sudah sangat jelas tidak mempunyai surat kepemilikan hak atas tanah tersebut dan keterkaitannya dengan pihak KUA Kabupaten Siak selaku Tergugat II yang membuat atau menerbitkan Akta Ikrar Wakaf. Maka dari itu pihak KUA selaku Tergugat II dan Pihak Tergugat I melanggar beberapa ketentuan dalam UUD perwakafan dan Kompilasi Hukum Islam.